In-situ blast vibration monitoring in cemented rockfill stope – a case study. Issue 2 (17th February 2017) - Emad, Muhammad Zaka; Mitri, Hani; Kelly, Cecile
Abstract: Sublevel stoping methods with delayed backfill are employed for mining tabular steeply dipping ore bodies. Cemented rockfill (CRF) is a type of backfill with simple operation, moderate capital cost while acquiring good strength. CRF stope is subjected to blast-induced vibrations during production blasting in adjacent stopes. Excessive dynamic load may destabilise backfill stope that leads to dilution of precious ore. Blast-induced vibrations can be monitored to assess the stability of CRF and to determine the blast waveforms for a detailed analysis using numerical models. This paper aims to establish that excessive blast-induced vibrations are the prime cause of backfill dilution at the case study mine. A detailed methodology and results of monitoring blast-induced vibrations in backfill are also presented. Blast vibrations are monitored in a CRF stope using three dimensional geophones and blast vibration monitors. The monitoring results obtained are processed and analysed to produce results in terms of velocity components and vector sum of velocity components. The data is further processed to examine particle velocity vs. scaled distances of individual blastholes and the effect of rock/backfill interface